2010
DOI: 10.1029/2009ja014714
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of background levels for the Wind WAVES instrument and implications for the galactic background radiation

Abstract: [1] We investigate and predict the observed background levels for the TNR, RAD1, and RAD2 receivers when connected to the X, Y, and Z antennas of the WAVES instrument on the spacecraft Wind. The receivers are connected to either a single antenna, in "SEP" mode, or a combination of antennas, in "SUM" mode. With the TNR receiver in SEP (X) mode, the predicted backgrounds agree to within 20% when modeled using a two component model for the quasi-thermal plasma noise (QTN). Calibrating the RAD1 in SEP (X) mode obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…The background model of Hillan et al [2010, Figure 13] is used to predict B ( f ) as a function of frequency (in W m −2 Hz −1 ) over the entire frequency range of the Wind/WAVES instrument (4‐13825 kHz [ Bougeret et al , 1995]). This model includes contributions from galactic background radiation, dominant at high frequencies above around 300 kHz, local quasi‐thermal plasma noise, dominant at low frequencies below around 300 kHz, and receiver noise.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The background model of Hillan et al [2010, Figure 13] is used to predict B ( f ) as a function of frequency (in W m −2 Hz −1 ) over the entire frequency range of the Wind/WAVES instrument (4‐13825 kHz [ Bougeret et al , 1995]). This model includes contributions from galactic background radiation, dominant at high frequencies above around 300 kHz, local quasi‐thermal plasma noise, dominant at low frequencies below around 300 kHz, and receiver noise.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The channel frequency spacing varies with the three receivers that span the Wind/WAVES frequency range. However, in the range where much of the observed type II emission occurs (typically ≈ 20 kHz − 1 MHz), the frequency spacing is normally no greater than 4 kHz [ Bougeret et al , 1995; Hillan et al , 2010]. We convert the flux of the dynamic spectrum into a relative decibel scale using TB(t,f)=10log[(T(t,f)+B(f))/B(f)], where T B ( t , f ) is the dynamic spectrum in relative flux units (dB).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…(A factor of 10 in the factor ( O ( t , f ) + B ( t , f ))/ B ( t , f ) then corresponds to a difference of 10 dB in DB O ( t , f ).) A model for the WAVES instrument's observed background, including galactic background radiation and quasithermal plasma noise from the solar wind plasma, is presented in Hillan et al [2010] and used here. The dynamic spectra DB O ( t , f ) plotted in Figure 2 are all measured in dB relative to the observed radio and instrument background as per .…”
Section: Type II Observationsmentioning
confidence: 99%
“…However, this analysis was not fully quantitative and lacked a comprehensive model of the observed satellite background to be incorporated into theoretical spectra for detailed comparisons between theory and observation. A recent model by Hillan et al [2010] of the background observed by the WAVES instrument onboard the spacecraft Wind allows us to directly compare the predicted type II spectra with spacecraft observations and to quantitatively investigate the agreement between theory and observation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation